Solid-Lattice Stem Optimization Design for Hip Implants - Castro Vera, Kleber Leonardo; Al-Jweijati, Mustafa (International Journal of Engineering and Management Sciences, 2020)
The goal of this study is analyzed and design a methodology to reduce stem mass, through topology and lattice optimization of a Ti-6Al-4V hip implant, meeting yield stress requirements. Four optimization cases were studied: Topology optimization (1), Lattice design 100% (2), Lattice design 50% (3), Lattice design 25% (4). Five load cases from a study were applied for each optimization cases: Combined (LC1), standing-up (LC2), standing (LC3), going up stairs (LC4), jogging (LC5). The optimized cases design reduced stem mass approximately by 30% (1), 5% (2) ,8% (3) and 2% (4), compared with the total stem hip Ti-6Al-4V implant.